Is transoral incisionless fundoplication (TIF) an answer to post-peroral endoscopic myotomy gastroesophageal reflux? A multicenter retrospective study - Brewer Gutierrez, Olaya I.; Chang, Kenneth J.; Benias, Petros C.; Sedarat, Alireza; Dbouk, Mohamad H.; Godoy Brewer, Gala; Lee, David P.; Okolo III, Patrick I.; Canto, Marcia I.; Khashab, Mouen A. (Endoscopy, 2021)
Background: The use of peroral endoscopic myotomy (POEM) for achalasia has a high incidence of post-procedural gastroesophageal reflux (GER). Transoral incisionless fundoplication (TIF) may be an ideal endoscopic treatment. We report our experience with the use of post-POEM TIF.Methods: In this multicenter retrospective study, post-POEM patients with GER who underwent TIF were included. The study end points were: (i) technical success; (ii) safety; (iii) effectiveness (changes in symptoms, scores, proton pump inhibitor [PPI] use, pH studies).Results: 12 patients underwent TIF after POEM, nine of whom had daily symptoms, with 91.7% requiring twice daily (BID) PPIs. Technical success was achieved in all patients. Two adverse events occurred. There were significant decreases in the percentage of patients on BID PPIs (P = 0.03), frequency of daily symptoms (P = 0.03), Reflux Severity Index questionnaire, and GERD Health-related Quality of Life scores (P = 0.03 and P = 0.003; n = 6). pH studies performed in seven of the patients showed a significant reduction in the mean DeMeester score (P = 0.05) and mean percentage acid exposure time (P = 0.04). Conclusion: Our experience suggests that TIF may be effective and safe in treating GER after POEM. Larger prospective trials are needed.